2011
DOI: 10.1002/eji.201041292
|View full text |Cite
|
Sign up to set email alerts
|

Altered purinergic signaling in CD73‐deficient mice inhibits tumor progression

Abstract: CD73/ecto-5 0 -nucleotidase dephosphorylates extracellular AMP into adenosine, and it is a key enzyme in the regulation of adenosinergic signaling. The contribution of host CD73 to tumor growth and anti-tumor immunity has not been studied. Here, we show that under physiological conditions CD73-deficient mice had significantly elevated ATPase and ADPase activities in LN T cells. In a melanoma model, the growth of primary tumors and formation of metastasis were significantly attenuated in mice lacking CD73. Amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
139
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(152 citation statements)
references
References 55 publications
9
139
0
2
Order By: Relevance
“…In line with these results, Salmi's group 18 and ours 20 found that loss of CD73 expression in mice resulted in increased infiltration of CD8 + T cells into tumor tissue.…”
Section: On Cd8supporting
confidence: 67%
See 1 more Smart Citation
“…In line with these results, Salmi's group 18 and ours 20 found that loss of CD73 expression in mice resulted in increased infiltration of CD8 + T cells into tumor tissue.…”
Section: On Cd8supporting
confidence: 67%
“…22 Because CD73 expression on hematopoietic cells, and not on nonhematopoietic cells, significantly influenced systemic antitumor CD8 + T cell immunity, we conclude that CD73 has distinct roles in hematopoietic and nonhematopoietic cells in limiting adaptive immune responses. Another unique mechanism has been proposed by Salmi's group 18 in which altered purinergic signaling in the absence of CD73 affects intratumoral infiltration of Tregs and intratumoral differentiation of type 1 macrophages (M1) into tumor promoting type 2 macrophages (M2), which are two key events in this tumor immune evasion process. This particular mechanism is likely important to our understanding of the diverse CD73-mediated adenosinergic effects in the tumor microenvironment, although the overall pathophysiological significance of the ratio of adenosine to ATP regulated by CD73 remains to be resolved.…”
Section: On Cd8mentioning
confidence: 99%
“…5,6,7 These antitumor effects were largely dependent upon the activation of CD8 C T cells, NK cells and production of IFNg. 5,6,8 Altogether, these observations indicated that the inhibition of the CD73 pathway deterred adenosine accumulation, and thus reversed immune suppression. Indeed, anti-CD73 mAb treatment is effective in inhibiting the growth of primary tumors and their metastases in mice.…”
Section: Introductionmentioning
confidence: 75%
“…Activation of A2a or A2b adenosine receptors on effector leukocytes typically (but not always) drives anti-inflammatory or immunosuppressive responses (78 -80). Thus, the relative concentrations of ATP versus ADP versus AMP that dynamically accumulate in the extracellular microenvironment of apoptotic tumor cells in vivo can variously skew local immune signaling networks between pro-inflammatory versus anti-inflammatory or immunogenic versus tolerogenic settings with significant consequences on the development of immunogenic anti-tumor responses (81)(82)(83)(84)(85)(86). Moreover, most types of tumor cells per se express different cassettes of P2 purinergic or P1 adenosine receptors that can modulate cell growth, survival, and sensitivity to pro-apoptotic mediators.…”
Section: Elevated Expression Of Panx1 Channels In Leukemic Versus Normentioning
confidence: 99%